Agricultural Technology Information Centre (ATIC): Farmers' Perception - M. A. Dar , Safeer Alam , Jasvinder Kaur , D. Ram , Shafiqul Islam and A. M. Tantray, (Indian Journal of Extension Education, 2014)
The present study was conducted for impact assessment of ATIC by measuring the level of satisfaction of the farmersvisiting the ATIC. Data from 59 farmers were collected who visited and registered at ATIC, SKUAST-Kashmir during lastfour years (2006-2010). The selection of farmers was made by random sampling technique. The data collected with thehelp of pre-structured interview schedule and analyzed to assess the level of satisfaction. ATIC products, services andinformation were rated very important and useful, but the respondents were dissatisfied with the availability ofproducts, services and informations provided to the farming community. It is, thus, recommended that thereshould be some improvement in the availability of quality products and other services and information to beprovided to the farmers.